Pathological features and clinical behavior of Lynch syndrome-associated ovarian cancer - Ryan, N.A.J. (Gynecol Oncol, 2017)
OBJECTIVE: Lynch syndrome (LS) is an inherited tumor predisposition condition caused by mutations in the mismatch repair (MMR) genes. Mutation carriers are at increased risk of various malignancies, including ovarian cancer (OC). Relatively little is known about the pathological features and clinical behavior of LS associated OC. METHODS: We analyzed the data of 1047 proven MMR mutated individuals from a prospectively maintained database at a large referral center for genomic medicine in the North West of England. Data were crosschecked with pathology reports, the National Cancer Registry and death certificates, where appropriate. Data from gynecological surveillance and risk reducing surgery were analyzed. RESULTS: We identified 53 cases of LSAOC in proven MMR mutated individuals. The cumulative risk of LSAOC was 20% at age 80 in those who retained their ovaries. LSAOC presented at an earlier age (average 51, range 24–70 years) than sporadic OC. The predominant histological subtype was endometrioid adenocarcinoma (53%). Most cases presented early (85% at stage I/II vs. 15% at stage III/IV, p < 0.001) and overall survival was excellent (80% 5-year survival), however, patients with advanced disease had a poor prognosis (40% 5-year survival). Most women were found to have LS after their OC diagnosis, however, two were detected at Stage 1c through gynecological surveillance and a further three were detected following surgery for screen-detected synchronous endometrial pathology. CONCLUSION: The predominance of early stage disease in LSAOC is linked to its good prognosis. We support risk-reducing surgery for women whose families are complete especially if undertaking hysterectomy for endometrial risk, and ovarian surveillance as part of gynecological screening for those who have not.